The Effect of Various Surface Treatment on the New Digitally Manufactured Materials Versus the Conventional Materials – In Vitro Study - Qutub, Osama Ahmed (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Clinical benefits of resilient denture liners have been recognized in prosthodontic practice for many years. The elastic behavior of the soft lining materials is designed to distribute functional and non-functional stress on denture-supporting tissues. Materials and Methods: A total of 30 dumbbell-shaped test specimens were prepared from two different heat cure denture base materials. They are divided into two groups. Group (A) was prepared from heat cure poly-methylmethacrylate resin (PMMA) and Group (B) was prepared from computeraided design and computer-aided manufacturing (CAD/CAM) acrylic resin denture base material. A temporary soft-liner type was used. The denture base specimens of (Group A and Group B) were subdivided equally into three subgroups. 3 mm was marked and sectioned on the specimens with fissure burs and removed to create a uniform space for the application of soft liner. The interface surface of each specimen and the denture base resin surface were conditioned by three surface treatment modalities: 1 – specimens were polished using silicone carbide papers of grit size, 2 – using air abrasion by 50 μm aluminum oxide particle, 3 – by application of 3 M Scotchbond dental adhesive. Tensile bond strength (TBS) was tested for the specimens of each subgroup after thermocycling. Results: The mean of TBS of subgroup (A3) and subgroup (B3) specimens treated with 3M Scotch bond was significantly higher than the other subgroups. Conclusion: The surface treatment of PMMA and CAD/CAM denture base specimens with primer followed using an adhesive bond of 3M Scotch bond had an effective and superior TBS.